Boundary observer design for cascaded ODE — Hyperbolic PDE systems: A matrix inequalities approach. (September 2020) - Ferrante, Francesco; Cristofaro, Andrea; Prieur, Christophe
Abstract: Boundary observer design for a system of ODEs in cascade with hyperbolic PDEs is studied. An infinite dimensional observer is used to solve the state estimation problem. The interconnection of the observer and the system is written in estimation error coordinates and analyzed as an abstract dynamical system. The design of the observer is performed to achieve global exponential stability of the estimation error with respect to a suitable norm and with a tunable convergence rate. Sufficient conditions in the form matrix inequalities are given for the design of the observer. The effectiveness of the approach is shown in a numerical example.